2022
DOI: 10.1111/poms.13445
|View full text |Cite
|
Sign up to set email alerts
|

Inventory Management Practices in Private Healthcare Facilities in Nairobi County

Abstract: U niversal health coverage (UHC) is an integral part of the United Nations sustainable development goals. The private sector plays a prominent role in achieving UHC, being the primary source of essential medicines for many people. However, many private healthcare facilities in low-and middle-income countries (LMICs) have insufficient stocks of essential medicines. Simultaneously, these same facilities carry excessive quantities of other drugs, leading to obsolescence. This suggests poor inventory control. To p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Periodic automatic review practices such as these, where a target inventory level is set, inventory is checked regularly, and orders are placed at uniform intervals, are widely accepted due to the ease of use and have largely been ignored in terms of cost and service‐level impact. While research on this topic has been relatively scant, past research has suggested that such widespread practices create significant supply and demand mismatches (Karamshetty et al., 2022).…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…Periodic automatic review practices such as these, where a target inventory level is set, inventory is checked regularly, and orders are placed at uniform intervals, are widely accepted due to the ease of use and have largely been ignored in terms of cost and service‐level impact. While research on this topic has been relatively scant, past research has suggested that such widespread practices create significant supply and demand mismatches (Karamshetty et al., 2022).…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…Furthermore, due to variations in distribution charges and bill payment periods, firms that regularly manage their inventory may face significant inventory expenditures (Yu and Cheng, 2014). Karamshetty et al (2022) concluded that inventory-related problems often occur due to resource limitations, managerial issues and market mechanisms. Addressing this issue is also an essential part of IM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/1754-2731.htm implement all the practices due to budget constrain Karamshetty et al (2022). Hence, there is a need for trade-off between practices and budget constraints for efficient use of resources.…”
Section: Introductionmentioning
confidence: 99%
“…Karamshetty et al. (2022) offer a detailed description of the often informal way in which inventory decisions are made at a selection of healthcare facilities in Nairobi.…”
Section: Five Areas Where Humanitarian Responses Can Be More Sustainablementioning
confidence: 99%
“…One survey respondent cautioned, based on a study in Nairobi, that software systems for inventory control may be counterproductive in developing countries, as simple manual or intuition-based systems may be more suitable in settings with small scale, low IT literacy, and high staff turnover. Karamshetty et al (2022) offer a detailed description of the often informal way in which inventory decisions are made at a selection of healthcare facilities in Nairobi.…”
Section: 54mentioning
confidence: 99%